PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN SEPATU GUNUNG PADA TOKO MOKZHAWARE TANGERANG SELATAN - Fadli Fatur Rachman; Syafieq Fahlevi Almassawa (YBAMB, 2024)
This research aims to determine the influence of product quality and service quality on purchasing decisions for Mount Mokzhaware shoes. The method used is a quantitative descriptive method with an associative approach. The sampling technique used is Probability Sampling, a sampling method using the Slovin formula. Data analysis uses regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. The results of this research are that product quality (X1) and service quality (X2) have a positive and significant effect on purchasing decisions (Y) with the regression equation Y = 1.219 + 0.122X1 + 0.595X2. The coefficient of determination has a simultaneous effect of 59.7%. Partially testing the hypothesis obtained a Product Quality figure of tcount > ttable or (11.019>1.98498). So H0 is rejected and H1 is accepted. This means that there is a positive and significant influence between the independent variables, namely Product Quality (X1) on Purchasing Decisions (Y). Service Quality figures are tcount > ttable or (10,662>1.98498). So H0 is rejected and H2 is accepted. This means that there is an influence between the independent variable, namely Product Quality (X2) on Purchasing Decisions (Y). Hypothesis testing obtained a value of calculated > F or (71.016 > 3.09). Thus, H0 is rejected and H3 is accepted, meaning that Product Quality (X1) and Service Quality (X2) together have a positive effect on Purchasing Decisions (Y).